Precision-cut rat placental slices as a model to study sex-dependent inflammatory response to LPS and Poly I:C - Anandam, Kasin Yadunandam; Abad, Cilia; Synova, Tetiana; Vinas-Noguera, Mireia; Bolboli, Bahareh; Vokral, Ivan; Karahoda, Rona; Staud, Frantisek (Frontiers in Immunology, 2022)
Maternal inflammation in pregnancy represents a major hallmark of several pregnancy complications and a significant risk factor for neurodevelopmental and neuropsychiatric disorders in the offspring. As the interface between the mother and the fetus, the placenta plays a crucial role in fetal development and programming. Moreover, studies have suggested that the placenta responds to an inflammatory environment in a sex-biased fashion. However, placenta-mediated immunoregulatory mechanisms are still poorly understood. Therefore, we have developed a model of ex vivo precision-cut placental slices from the rat term placenta to study acute inflammatory response. Rat placental slices with a precise thickness of 200 µm were generated separately from male and female placentas. Inflammation was stimulated by exposing the slices to various concentrations of LPS or Poly I:C for 4 and 18 hours. Treatment of placental slices with LPS significantly induced the expression and release of proinflammatory cytokines TNF-α, IL-6, and IL-1β. In contrast, Poly I:C treatment resulted in a less-pronounced inflammatory response. Interestingly, the female placenta showed higher sensitivity to LPS than male placenta. Anti-inflammatory agents, curcumin, 1α,25- dihydroxyvitamin D3, and progesterone attenuated the LPS-induced proinflammatory cytokine response at both mRNA and protein levels. We conclude that rat placental slices represent a novel alternative model to study the role of sexual dimorphism in the acute inflammatory response and immune activation in pregnancy.